Vic-dioxime complexes bearing carboxyester and picolyl amide functionality: synthesis, characterization, spectroscopy, electrochemistry, and electrical properties - KOCA, ATIF; DUMLUDAĞ, FATİH (SPRINGER WIEN, 2013)
We have synthesized a vic-dioxime, [(1Z,2Z)-bis(2-oxo-2-(pyridin-2-ylmethylamino)ethyl)-N'1,N'2-dihydroxyethanebis(imidothioate)] (LH4) via dimethyl 2,2'-(1,2-bis(hydroxyimino)ethane-1,2-diyl)bis(sulfanediyl)diacetate (LH2) and 2-(aminomethyl)pyridine by using the condensation technique. The formation of mononuclear (Ni(II), Cu(II)) and homodinuclear (LH)(2)(UO2)(2)(OH)(2)) complexes of LH2 and mononuclear Cu(II) and homotrinuclear ((LH)(2)M-3, M=Cu(II) and Ni(II)) complexes of LH4 were also obtained simultaneously with metal:ligand ratios of 1:2, 2:2 and 1:2, 3:2, respectively. The structure of the dioxime and its complexes are proposed in accordance with the elemental analysis, NMR, UV-Vis, FT-IR, and MS-FAB spectral data. The voltammetric analyses of the complexes showed metal- and ligand-based signals. The redox chemistry of the complexes exhibited various oxidation states of the central metals of the complexes. DC and AC conductivity measurements were performed at room temperature under vacuum in the dark. I-V characteristics of the complexes showed ohmic behavior. AC conductivity of the homotrinuclear copper and nickel increased and impedance of the same complexes decreased with increasing frequency.
Keywords: Vic-dioximes; Ester condensation; Water-soluble complexes; Ionophore; Transition metal complexes; Cyclic voltammetry; Conductivity; Impedance; DINUCLEAR COMPLEXES; NI COMPLEX; (E,E)M M; LIGAND; MONONUCLEAR; MOIETIES; OXIME